Functional relationship among social conditional stimuli, joint attention, tact and mand in children with autism (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
Deficits in joint attention (JA), characterized as response to joint attention (RJA) and initiation of joint attention (IJA), have been related to language problems seen in people with autism. The establishment of the behavior of others as discriminative/reinforcer conditioned stimuli can be important for JA. This study investigated functional relationships that can occur between the establishment of another person's behavior as discriminative/reinforcer conditioned stimuli and RJA, IJA, mand and tact repertoires in three children with autism. Compliance repertoires were trained and the reinforcing/ discriminative effectiveness of social conditional stimuli, RJA, IJA, mand and tact were pre-tested. Based on the initial assessment diferente baselines were constructed between the participants to initiate the training of nonexistent repertoires and to be able to evaluate the effects of one or more repertoires on the others. The results suggest a functional independence between the acquisition of RAC, mand and tact and the establishment of responses to social stimuli.
Keywords: joint attention; mand; tact; social conditional stimuli; autism